Cypriot Writers of the Diaspora - Herodotou, Maria (Études helléniques / Hellenic Studies, 2014)
In this paper an attempt is being made to present Greek Cypriot writers of the post-World War II era, who reside in major centres of the Greek Diaspora (or who lived there for a number of years), such as Great Britain, Australia, Canada and the USA, where they have produced their literature. My aim is to provide interested researchers or readers a guide to these writers and their work, as well as to acknowledge their contribution to both their homeland and their new country. The writers are presented alphabetically. This presentation is not complete, as many factors have limited the scope of my research. I hope that it will be expanded at a later stage.